Reconstructing Realism in Post-Postmodern Narrative: Dave Eggers’s A Heartbreaking Work of Staggering Genius - Bolaño Quintero, Jesús (Complutense Journal of English Studies, 2021)
By analysing Dave Eggers’s autofictional work A Heartbreaking Work of Staggering Genius, this article attempts to reveal the role of this author in the post-postmodern narrative of the turn of the millennium. Following in the wake of David Foster Wallace, Eggers’s solution to overcome the problems created by postmodernism is a kind of writing based on honesty. Through a rebirth of the author, the objective of Eggers’s New Sincerity is the democratization of narrative in order to create a sensibility network aimed at ending the solipsism brought about by postmodern linguistic relativism. However, this new sensibility is reminiscent of pre-postmodern fundamentalism. The use of meta-metafiction based on the use of neo-Romantic irony enables Eggers to create an escape valve that allows for the creation of a metamodern oscillation—as described by Tim Vermeulen and Robin van den Akker.